A new species of Liphanthus from Peru (Hymenoptera: Andrenidae) - Gonzalez, Victor H.; Rasmussen, Claus; Engel, Michael S. (Journal of Melittology, 2014)
The protandrenine bee genus Liphanthus Reed (Panurginae: Protandrenini) is currently known from Chile and Argentina. Liphanthus (Melaliphanthus) cuscoensis Gonzalez, Rasmussen, & Engel, new species, is described and figured from a male collected in Cusco, Peru, at 4167 meters of elevation. This finding represents the northernmost record for the genus and the fourth protandrenine species described from Peru. An updated key to the species of the subgenus Melaliphanthus Ruz & Toro is provided.